Przewalski's horse - Wilcox, Charlotte. frey50 (Mankato, Minn. : Capstone Press, 1997)
Discusses the last truly wild equine species, which has been extinct in the wild since the 1960s but was recently reintroduced into its native habitat in Mongolia.
Keywords: Przewalski's horse -- Juvenile literature; Przewalski's horse; Horses